Memórias e envelhecimento : narrativas de professores universitários aposentados - Ilha, Vanessa Domingues (2011)
The main objective of this study was to analyze the life histories of retired teachers from the University of Passo Fundo to recall his memories, his memories to elucidate and understand how they constructed their identities. Analyzing life trajectories from the collective memory is a way to understand how this triggers the building this past history. Also we understand retirement, kept a few exceptions such as professional step that accompanies aging in humans (physiological), since, chronologically, both occupy the same decimal age. Each one has with its equal relationships that allow them to contribute your story to be told, they too will be part of recollections from what was experienced together. Observing recounted memories from childhood, school and vocational training, retirement and after retirement, the prospect of contemporary made through the narratives of life histories is a closer relationship between past and present. The study of memories and narratives of the life histories of a group of retired teachers allows us to know the history of each one since the initial training until retirement, the peculiarities and coping strategies for the reorganization of life projects until the move to inactivity. In terms of methodology, qualitative research, multidisciplinary, allows one to respond to particular issues, it generally can not be quantified because they cover the universe of subjectivity.